Вплив гальмування дислокацій у процесі пластичної деформації на фотолюмінесценцію іонів Mn2+ в монокристалах ZnS - Prokofiev, T.A.; Ivanchenko, A.V. (Publishing house "Academperiodika", 2022)
Experimental photoluminescence spectra of Mn2+ ions in single-crystalline ZnS specimens under various plastic deformations have been studied. Features in the photoluminescence spectra of specimens destroyed at small deformations are found. By resolving the spectra, individual spectral bands caused by the emission of Mn2+ ions with different local environments in ZnS single crystals subjected to various plastic deformations are obtained. Changes in the fraction of emitting Mn2+ ions in ZnS single crystals owing to changes in the plastic deformation magnitude are calculated for each individual band. A new individual band with a maximum emission at λmax ≈ 588 nm is identified, and an explanation is proposed for the mechanism of its appearance at the displacement, hindering, and stopping of partial dislocations in the course of plastic deformation.